2014
DOI: 10.3892/or.2014.3460
|View full text |Cite
|
Sign up to set email alerts
|

XAV939 promotes apoptosis in a neuroblastoma cell line via telomere shortening

Abstract: Abstract. Telomeres, telomerase and tankyrase (TNKS) have an extremely important and special association with human cell aging and cancer. Telomerase activity is abnormally high in cancer cells and is accompanied by the overexpression of tankyrase 1 (TNKS1). TNKS1 is a positive regulator of telomerase activation and telomere extension in the human body, indicating that TNKS1 may be a possible therapeutic target for cancer. XAV939 is a small-molecule inhibitor of TNKS1. The objective of the present study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Our data are consistent with Tnks inhibitorinduced telomeric shortening independent of changes to the Wnt signaling status in this cell line. We note that another study using XAV-939 observed similar effects on telomere length maintenance in a neuroblastoma cell line, thereby extending the relevance of our findings to other cell types (35). Taken together, our findings reveal a single-agent strategy for inducing telomerase shortening that is distinct from current efforts devoted to directly targeting telomerase.…”
Section: Resultsmentioning
confidence: 46%
“…Our data are consistent with Tnks inhibitorinduced telomeric shortening independent of changes to the Wnt signaling status in this cell line. We note that another study using XAV-939 observed similar effects on telomere length maintenance in a neuroblastoma cell line, thereby extending the relevance of our findings to other cell types (35). Taken together, our findings reveal a single-agent strategy for inducing telomerase shortening that is distinct from current efforts devoted to directly targeting telomerase.…”
Section: Resultsmentioning
confidence: 46%
“…XAV939 is an inhibitor of tankyrase, a positive regulator or telomerase. It has been shown to induce apoptosis in the telomerase expressing neuroblastoma cell line SH-SY5Y [70].…”
Section: Drugs Targeting Telomerase Activitymentioning
confidence: 99%
“…Also, tankyrase 1/2 inhibitors such as XAV935 and XAV939 may have promising effects in progressed and chemoresistant relapsed NB. They were reported to increase apoptosis by the induction of telomere shortening, prevent chemoresistance and inhibit WNT-β-catenin signaling, even in MYCN-amplified tumors [70,71,104,105]. However, NB is a tumor of children and most cases occur in young children.…”
Section: Are Wnt Pathways Druggable In Nb?mentioning
confidence: 99%